Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jpeds.2016.10.044
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Breast Milk Sodium to Potassium Ratio and Maternal Report of a Milk Supply Concern

Abstract: We report here that among exclusively breastfeeding mothers at day 7 postpartum, those with milk supply concerns were significantly more likely to exhibit biochemical evidence of less progress toward mature lactation (elevated milk Na:K). Furthermore, elevated milk Na:K was predictive of early weaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 16 publications
(25 reference statements)
1
41
1
Order By: Relevance
“…It has been reported that human milk sodium drops from 60 mM to 10 mM between days 1 and 5 postpartum, this precipitous drop reflects tight junction closure [ 2 ]. Delayed onset of secretory activation is established as a risk factor for poor lactation outcomes [ 3 ] with high sodium concentrations at day 7 considered a risk factor for the cessation of breastfeeding [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that human milk sodium drops from 60 mM to 10 mM between days 1 and 5 postpartum, this precipitous drop reflects tight junction closure [ 2 ]. Delayed onset of secretory activation is established as a risk factor for poor lactation outcomes [ 3 ] with high sodium concentrations at day 7 considered a risk factor for the cessation of breastfeeding [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is mirrored by changes in the human milk transcriptome during this period and is therefore considered more accurate than using time postpartum to define lactation stage [ 5 ]. Changes in the Na:K ratio form a continuum over the first week postpartum, with a high Na:K ratio on day 7 (>0.8) [ 4 ] indicative of suboptimal milk supply or feeding problems and consequently a higher risk of breastfeeding cessation. An elevated ratio on day 7 is associated with 3.3 times greater odds of stopping breastfeeding in mothers reporting concerns about milk supply [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarkers: by 72 hours, compositional changes in colostrum, reflecting paracellular junction closure directly relate to early, frequent, and effective colostrum removal and are predictors of the adequacy of future production and infant intake. [19][20][21] Nomograms predicting weight loss per hour of life can help determine infants at the extremes for excessive weight loss. As early as 6 hours, weight loss differentials for term infants at risk for excessive weight loss (>10%) are evident.…”
mentioning
confidence: 99%